Resisting “the World of the Powerful”: “Wild” Steam and the Creation of Yellowstone National Park - Graham, Chelsea (Frontiers in Communication, 2021)
In this essay, I argue that steam operates as a critical, other-than-human actor in the establishment of Yellowstone National Park and a broader, colonial posture towards the natural world that reflects a sharp division between nature and culture on the settler landscape—reiterating what Marisol de la Cadena and Mario Blaser call “the world of the powerful,” and a “world where only one world fits” (2018, pp 2-3). By appearing in contradictory contexts of powerful engines and pristine nature, steam was bifurcated into natural and cultural registers in order to justify the establishment of the natural park and the colonists’ claim to Yellowstone as “property,” foreclosing alternative relationships to the land such as those of the region’s Indigenous residents. Approaching this research from the perspective of a settler on Indigenous lands, I am invested in engaging new materialist and ecological methodologies in the important work of decolonial critique. Adopting Nathen Stormer’s (2016) “new materialist genealogy” and Nathaniel Rivers’ (2015) treatment of wildness in service of a decolonial agenda, I demonstrate how steam’s inherent repulsion to nature/culture dichotomies contests the very idea of the park itself, Yellowstone’s importance to the settler state’s expansion into the west, and its popular understanding as an exemplar of environmental politics. Further, this essay provides a methodological and theoretical intervention for new materialist and ecological scholarship to support decolonial projects in solidarity with Indigenous resistance. By unraveling dominant discourses that persist in collective identification with Yellowstone, the borders of the park that denote iconicity and exemplarity, unspoiled nature from capitalist development, become brittle, fragile, and so, too, does their dominance in discourses about environmentalism. By disrupting Yellowstone and undermining its dominance, we can demonstrate, unequivocally, that another world—indeed worlds—are possible.